Delirium in patients with advanced cancer - Costa, Isabel (Portuguese Journal Internal Medicine, 2002)
Cognitive disorders are very common in cancer patients. Delirium is one of the most frequent neuropsychiatric complications in patients with advanced cancer. It may be reversible except in terminal patients. Delirium is often not diagnosed by health-care professionals, in elderly medical patients. Acute onset of a fluctuating level of awareness, accompanied by sleep-wake cycle disruption, lethargy or agitation, and nocturnal worsening of symptoms, is diagnostic of this condition. The author make a revision of the clinical features, aetiology, diagnosis and management of delirium.